Sustainable purchasing as an environmental management strategy at the Institute of Exact and Natural Sciences at the Federal University of Pará (Research, Society and Development, 2023)
The unsustainable consumption worldwide has caused significant environmental imbalances to our planet. Factors contributing to this include the lifespan, computerization, and media encouragement of consumption. These factors lead to environmental destruction, deterioration, and pollution. In this context, Federal Institutions of Higher Education (IFES) cannot evade the duty to promote greater sustainability through their procurement, as they are public educational institutions that play a central role in society. As disseminators of information, they are significant consumers of resources, thus responsible for both production and consumption. the aim of this study was to describe the situation at the Institute of Natural Exact Sciences of the Federal University of Pará (ICEN/UFPA) concerning the rational use of its natural resources and office materials. The study analyzed the on-site application of these resources that are part of UFPA's procurement agenda. This research investigated the importance of sustainable procurement activities at ICEN in relation to the work of its administrative staff. The methodology employed involved field research, a review of specialized literature, examination of legislation, and finally, the implementation of a questionnaire containing closed-ended questions submitted to the technical-administrative staff working at ICEN. As a result, strengths and weaknesses were identified in ICEN's management, such as the lack of sustainable practices in its routine and insufficient planning when requesting resources through the procurement agenda. The final product of this research was the development of a handbook outlining best practices for environmental sustainability.